Exploring the determinants for airport profitability: Traffic characteristics, low-cost carriers, seasonality and cost efficiency. (July 2017) - Zuidberg, Joost
Abstract: Given the growing pressure on aeronautical revenues, the increasing focus on airports' financial performance and the sharpened state aid guidelines in Europe, it is valuable to have detailed insight in the determinants for airport profitability. This paper fills in a gap in scientific research by presenting the most important traffic and financial determinants for airport profitability, since the majority of scientific literature on airport (financial) performance focuses on efficiency rather than on profitability. Comprehensive airport traffic and financial data for 125 airports in Europe, the United States (US), Canada, Australia and New Zealand for the period 2010–2016 have been used to estimate several fixed-effects panel data regression on profit margin. Among others, the results show evidence for the fact that an increasing share of transfer passengers affects an airport's profit margin. In addition, there is no sign of a general LCC effect and just limited evidence for the fact that the market share of specific LCCs affect airport profitability: only an increase in the market share of Southwest Airlines at major airports leads to lower profit margins. Moreover, a quadratic relationship between seasonality and profitability has been identified. It points at the existence of a certain optimal seasonality score. Below that tipping point, a decrease in seasonality leads to higher profit margins. On the contrary, a further reduction of seasonality after the tipping point leads to lower profit margins. This might indicate that no or limited seasonality is a result of capacity constraints and, in turn, leads to increasing operating costs related to congestion. Regarding financial variables, the results especially show significant positive effects of capital cost efficiencies on profitability. Those effects are especially large for airports in the US and for small regional airports. Labour productivity only plays a important role in the profitability of US airports. Finally, the results show that regional O/D airports largely depend on regional economic development and population growth, while the major airports rather depend on global economic development than on an increase in local demand.